Effect of entomopathogenic nematodes on populations of the coffee berry borer, Hypothenemus hampei (Coleoptera: Scolytidae), in berries on the soil - LARA-G., JUAN CARLOS; LÓPEZ-N., JUAN CARLOS; BUSTILLO-P., ALEX E. (Revista Colombiana de Entomología, 2004)
The effect of two native entomopathogenic nematodes Heterorhabditis sp.  (Rhabditida: Heterorhabditidae) and Steinernema sp. (Rhabditida:  Steinernematidae) was studied in doses of 125.000, 250.000 and 500.000 infective juveniles (IJ) per tree base on populations of the coffee berry borer, Hypothenemus hampei. During the  first coffee harvest of 2001, there were no statistical differences between treatments for the infestation level in the tree due to the high variability of the number of fruits with which the experiment began. For the second coffee harvest of 2001, the percentage of mortality of the coffee berry borer with the two species was 53 and 88%, a month after their application, statistically different (p